EVALUASI KELELAHAN MASINIS PT KERETA API INDONESIA DIVISI REGIONAL IV DENGAN MENGGUNAKAN SUSTAINED ATTENTION TEST (SAT) - Rafid Al Hazmi, Hilman
Fatigue is one of the main reason of accident happening during work. There is a strong correlation between fatigue and increasement in accident risk. Fatigue that connected to accident in railway transportation is the impact of decreasement in performance and attention. PT Kereta Api Indonesia has fatigue issues on their workers. 33% reasons of railways accidents in Indonesia on 2010 – 2016 caused by human factors. Fitness for duty is a procedure of preventing accident caused by fatigue that consist several tests before duty. Pre duty tests for machinist in PT Kereta Api Indonesia only accomodate physiological aspect. Therefore, a test is need to see the readiness of the machinist before doing their duty and monitor the condition after finishing their duty. A total of 10 coal machinists for each shifts participated in this study which aims to evaluate the condistion of machinist before and after finishing their duty. The tasks observed were the morning shift (06.00 – 14.00), afternoon shift (14.00 – 22.00), and evening shift (22.00 – 06.00). The route observed for the shifts is Tarahan – Ketapang. The measurement instruments consist of a test using a computer and several questionnaires. The test used was the Sustained Attention Test (SAT) which will display order of numbers for 10 minutes. The questionnaires used were the Karolinska Sleepiness Scale (KSS), Visual Analogue Scale (VAS), Morningness-Eveningness Questionnaire (MEQ), and Pittsburgh Sleep Quality Index (PSQI). Machinist will have the tests and questionnaire before duty and after duty. Then, machinist will do outside duty measurement, those are baseline for SAT (10 minutes SAT) and MEQ and PSQI questionnaire. The results showed that 73% of the machinist were the morning type and 67% of the machinist had insufficient sleep quality. Score of %miss SAT during morning shift before duty (14.15%) and night shift before (15.68%) and after duty (14.41%) indicates sustained attention level of machinists are bad, classification of KSS indicates machinists are in fatigue condition before (64% of participants) and after duty (77% of participants), VAS score during morning shift after duty (75.2), afternoon shift before (42) and after duty (80.5), night shift before (61.1) and after duty (81.2) indicates fatigue level of machinists are high. The fatigue experienced by the machinists was influenced by insufficient of sleep quality. This research shows that machinists have high level of fatiugue, and different shift did not affect the fatigue level of the machinists.